(What) do you believe?: Therapist spiritual/religious/non-religious self-disclosure. (4th May 2018) - Magaldi, Danielle; Trub, Leora
Abstract: Objective: Spiritual/religious/non-religious (S/R/N) identity development is often neglected in psychotherapy training and represents an area where psychotherapists feel they lack competence. Such feelings can become even more pronounced when it comes to S/R/N self-disclosure. This study explores the decisions therapists make regarding self-disclosure, which impacts the psychotherapy process.Method: This grounded theory study explores psychotherapists' S/R/N self-disclosure based on qualitative interviews with 21 psychotherapists representing varied theoretical orientations and spiritual, religious, atheist, and agnostic backgrounds.Results: Findings reveal that while some self-disclosure happens on an explicit level, more often psychotherapists find implicit ways to share S/R/N aspects of the self for purposes of enhancing the therapeutic alliance and to convey openness. Psychotherapists also attempt to avoid the topic altogether, either to protect the therapeutic relationship or because of unresolved S/R/N identity in the therapist.Conclusions: Developing skills related to S/R/N self-disclosure represents an important aspect of multicultural competence, which can impact clients' feelings of safety and comfort discussing their own S/R/N identity. This capacity is strongly influenced by the therapist's self-awareness regarding S/R/N identity. Suggestions for engaging S/R/N identity and disclosure in supervisory experiences and academic preparation are discussed.